Gaps in the Management of Hypertensive Patients in a Metropolitan Area of Havana - Armando Rodríguez Salvá; Alejandra Caridad Piña Alonso; Addys Díaz Piñera; René García Roche; Susana Balcindes Acosta (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Foundation: knowing and facing the difficulties which appear during the control of the hypertensive patient is a challenge for every health system. Objective: to identify the gaps in the management of hypertensive people in a metropolitan area of Havana. Method: a descriptive and cross-sectional study was conducted between February and June 2016 at the Nguyen Van Troi Polyclinic, in Centro Habana. Out of the total of 18 year-old or older 4480 people, who were identified as hypertensive, a sample of 531 was selected by means of a two-stage cluster sampling, studying 521. They were applied a semi-structured interview and blood pressure measurement, documents of the area were reviewed to identify other gaps. The variables analyzed in the study were: socio-demographic, access to health services, diagnosis and care, monitoring and control treatment. The numerical variables were presented with measures of central tendency and dispersion. Categorical variables were presented as frequencies and percentages. Results: a 92.3 % of the interviewees said they felt the need for care in the last year, of these, 80.7 % had access to health services. 98.1 % had indicated pharmacological treatment, with diuretics being the most used with 61 %. 50.7 % have adherence to treatment according to the Morisky test. 24.2 % were not seen by their doctor in the last year, the main reason was the no programming or appointment to consultation. 56.6 % had their blood pressure figures controlled. Conclusions: access gaps were linked to the lack of attention seeking despite perceiving the need. Poor follow-up and low therapeutic adherences in hypertensive people were the principles that supported the high percentage of individuals with uncontrolled blood pressure figures.